Harnessing Traditional Wisdom: Exploring the Intersection of Indian Millets, Agriculture, and Intellectual Property Rights (Journal of Intellectual Property Rights (JIPR), 2026)
India proposed the year 2023 to be celebrated as the International Year of Millets which was subsequently accepted and declared by the United Nations General Assembly (UNGA).1 Prior to that, year 2018 was declared as the national year of millets.2 The agenda was to create awareness and harness the untapped potential of millets for food security, nutrition, and sustainable agriculture. However, whether that alone is suffice to serve the purpose is a moot question. The author asserts that only when different aspect of millets and millet production are duly backed by intellectual property recognition (read protection and support) would a tangible change occur in the awareness bar-graph. By advancing IP protection for millets, the aim is to raise global awareness about their significance and to highlight them as deserving of the attention and recognition they warrant. Merely declaring years as ‘Millet Years’ is rhetorical; we need tangible actions, such as integrating IP strategies, to truly promote and protect millets for long-term impact. This approach, in the opinion of the author, is expected to position millets as valuable crops, encouraging their cultivation and consumption on a larger scale.India is a home to a large variety of agrarian crops and has a proportionally a larger workforce involved in it. Among other crops, millets have a significant share in the total agricultural production of the country, making India the largest producer in the world. However, agricultural practices in contemporary times with over-reliance on crops such as rice and wheat have led to a challenge to the soil health, climate change and commercialisation. If India’s contextual traditional knowledge is utilised, and millet production is ably supported by the IP regime, such as trademark and geographical indications, it would turn the tide in favour of expanding millet production and encouraging broader adoption, and possibly reducing food security issues.The paper analyses the present profile of Indian Agriculture and the placement of Indian millets in the same. And howthe tool of IP can be used to in protecting these super foods and incentivising the stakeholders engaged in the production ofmillets.When we talk of stakeholders—it means especially the farmers or the breeders or the practitioners of associated traditional knowledge, and the ones marketing the various millets and millet-based products to some extent. So, the paper touches upon three disciplines---Agriculture, IP Law and Commerce.The write-up is primarily doctrinal in nature, but the author has brought in a flavour of empirical into it as for the chapter on conclusions and for suggesting the way forward, interviews were conducted with 20 experts. They were administrators, academicians, policy makers and researchers in agriculture. The data gathered was aimed at identifying the key challenges and opportunities in promoting millet production and adoption in India. The purpose was to assess the potential of leveraging the Intellectual Property Rights (IPR) framework to incentivise stakeholders across the supply chain. This research seeks to provide actionable insights on how targeted policy and IPR strategies could drive sustainable millet cultivation, boost economic incentives, and support India's food security and nutrition goals. A specifically curated interview schedule was used to gather insights into the specific challenges they face in policy-making, growing/marketing millets. The insights gathered from these 20 experts, it is hoped, would strengthen the credibility of our proposals. It was challenging because target population is rare, hidden, or difficult to reach through traditional sampling methods.